Sports Ultrasound: Applications Beyond the Musculoskeletal System. (September 2016) - Finnoff, Jonathan T.; Ray, Jeremiah; Corrado, Gianmichael; Kerkhof, Deanna; Hill, John
Background: Traditionally, ultrasound has been used to evaluate musculoskeletal injuries in athletes; however, ultrasound applications extend well beyond musculoskeletal conditions, many of which are pertinent to athletes. Evidence Acquisition: Articles were identified in PubMed using the search terms ultrasound, echocardiogram, preparticipation physical examination, glycogen, focused assessment with sonography of trauma, optic nerve, and vocal cord dysfunction . No date restrictions were placed on the literature search. Study Design: Clinical review. Level of Evidence: Level 4. Results: Several potential applications of nonmusculoskeletal ultrasound in sports medicine are presented, including extended Focused Assessment with Sonography for Trauma (eFAST), limited echocardiographic screening during preparticipation physical examinations, assessment of muscle glycogen stores, optic nerve sheath diameter measurements in athletes with increased intracranial pressure, and assessment of vocal cord dysfunction in athletes. Conclusion: Ultrasound can potentially be used to assist athletes with monitoring their muscle glycogen stores and the diagnosis of multiple nonmusculoskeletal conditions within sports medicine.